Acute Respiratory Failure Is the Initial Manifestation in the Adult-Onset A3243G tRNALeu mtDNA Mutation: A Case Report and the Literature Review - Pan, Xiaoli; Wang, Lijun; Fei, Guoqiang; Dong, Jihong; Zhong, Chunjiu; Lu, Jiahong; Jin, Lirong (Frontiers in Neurology, 2019)
Isolated mitochondrial myopathy refers to the condition of mitochondrial disorders that primarily affect the skeletal muscle system. Here we report on a case of a patient who presented with acute respiratory failure as the initial and predominant clinical manifestation after using anesthetic drugs. The diagnosis of mitochondrial myopathy was made by histochemical findings of ragged red fibers with a modified Gomori trichrome Stain in the skeletal muscle biopsy and the genetic detection of an A3243G point mutation in the tRNALeu (UUR) gene of mitochondrial DNA (mtDNA) in a peripheral blood specimen. The patient revealed a benign clinical outcome with ventilator assistance and a cocktail treatment. Further, we performed a literature review on patients with respiratory failure as the early and predominant manifestation in adult-onset isolated mitochondrial myopathy. Eleven cases in nine studies (including our case) have been reported, and five of whom underwent DNA analysis all harbored the A3243G mutation in the tRNALeu gene of the mtDNA. Use of sedative drugs tends to induce acute respiratory failure in such cases.